Response of Vitis vinifera L. cv. Merlot to Low Frequency Irrigation and Partial Root Zone Drying in the Western Cape Coastal Region – Part II. Vegetative Growth, Yield and Quality - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2011)
The impact of five drip irrigation strategies on vegetative growth, yield and quality of Merlot/99R was compared to a non-irrigated control (T1) in the coastal region of the Western Cape province. Irrigations at pea size, véraison and post-harvest, either applied in grapevine rows (T2) or work rows (T4), tended to increase berry mass and yield compared to T1. More frequent irrigation at pea size, midway between pea size and véraison, at véraison, midway between véraison and harvest, and post-harvest, applied either in the grapevine rows (T3) or work rows (T5), increased berry mass and yield. A partial root zone drying (PRD) strategy, obtained by switching subsurface irrigation in the work rows between alternating rows at approximately 14-day intervals (T6), induced a similar trend. Under the given conditions, yield only increased when irrigation plus rainfall from bud break in September until harvest in February/March increased from ca. 200 mm to 400 mm. More water did not cause any further yield increases. Although low frequency irrigation increased yields compared to T1, it did not affect sensorial wine quality characteristics negatively. Non-irrigated grapevines produced the smallest berries, but did not necessarily produce wine superior in quality. The PRD strategy reduced wine quality, particularly when irrigation was applied at a high frequency between switches. The latter strategy only improved irrigation water productivity when compared to conventionally irrigated grapevines that received unnecessary high volumes of water. Subsurface irrigation applied in the work rows did not affect grapevine responses compared to irrigation in the grapevine rows.